Peripartum amniotic fluid embolism with disseminated intravascular coagulation during ongoing coronavirus disease pandemic – A case report (Indian Journal of Case Reports, 2020)
Amniotic fluid embolism (AFE) is a relatively rare but potentially catastrophic obstetric emergency. Early studies revealed mortality rates as high as 61–86%, but more recent estimates suggest a case fatality of 13–26% with adverse neonatal outcomes. The decrease in mortality can be because of the high index of suspicion and aggressive management practices. We report a case of AFE which manifested atypically with severe back pain and respiratory distress in operation theater before anesthesia induction for elective cesarean (lower segment cesarean section).